Mapping ecosystem services on brownfields in Leipzig, Germany - Pueffel, Catharina; Haase, Dagmar; Priess, Joerg A. (Ecosystem services, 2018)
•Ecosystem service use has been mapped with users on green urban brownfields.•Recreational activities dominated the use of cultural ecosystem services.•Urban brownfields were appreciated for providing less regulated, wilder green spaces.•Brownfields complement ecosystem services provided by formal urban green. Urban green brownfields are a particular type of urban green space and contribute to the quality of life by providing a variety of ecosystem services (ES). In this study, we mapped the use of ES and perception of disservices (EDS) on brownfields in the city of Leipzig using the smartphone application MapNat. We assessed the personal valuation and motives of users in relation to site and vicinity characteristics. Results suggest that brownfields play a particular role in the set of urban green spaces, providing characteristic ES such as opportunities to recreate, relax and retreat, partly differing from or complementing ES in formal urban green spaces. We identified spatial use patterns depending on local characteristics and personal preferences. For example, less accessible sites were relatively high valued and often used for dog-walking. Vice versa, better accessible sites were rather visited for informal stays and ‘hang-outs’. The patterns of use identified in this study may be of interest for urban management and planning of public green spaces, especially if no immediate follow up use or conversion of brownfields is planned.